A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 KAMPAR UTARA IN COMPREHENDING NEWS ITEM TEXTS - Adha, Arfina; Gultom, Effendy; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This descriptive research aims to find out the ability of the second year students of SMAN 1 Kampar Utara in comprehending news item texts. The population of this research was all of the second year students of SMAN 1 Kampar Utara in academic year 2017/2018. The number of sample was 22 students which were chosen by using cluster random sampling technique. The data were collected using reading comprehension test in multiple choice type by giving 5 news item texts with 40 multiple choice items. The results of the data analysis showed that the mean of the students’ score in compreheneding news item texts is 74.00. It can be concluded that the ability of the second year students of SMAN 1 Kampar Utara in comprehending news item texts is good. Based on the result of the students’ scores in each of reading comprehension component, the lowest component of reading comprehension for the students was in finding inferences (62.73) and the highest one was in finding factual information in sources (81.82).Keywords: Study, Ability, News Item Text.